Bacteria–Host Interactions in Multiple Sclerosis - Cossu, Davide; Yokoyama, Kazumasa; Hattori, Nobutaka (Frontiers in Microbiology, 2018)
Multiple sclerosis (MS) is caused by a complex interaction of genetic and environmental factors. Numerous causative factors have been identified that play a role in MS, including exposure to bacteria. Mycobacteria, Chlamydia pneumoniae, Helicobacter pylori, and other bacteria have been proposed as risk factors for MS with different mechanisms of action. Conversely, some pathogens may have a protective effect on its etiology. In terms of acquired immunity, molecular mimicry has been hypothesized as the mechanism by which bacterial structures such as DNA, the cell wall, and intracytoplasmic components can activate autoreactive T cells or produce autoantibodies in certain host genetic backgrounds of susceptible individuals. In innate immunity, Toll-like receptors play an essential role in combating invading bacteria, and their activation leads to the release of cytokines or chemokines that mediate effective adaptive immune responses. These receptors may also be involved in central nervous system autoimmunity, and their contribution depends on the infection site and on the pathogen. We have reviewed the current knowledge of the influence of bacteria on MS development, emphasizing the potential mechanisms of action by which bacteria affect MS initiation and/or progression.